On Neutrosophic Implicative Filters of BL-Algebra - Ibrahim, A.; Gunaseeli, S. Karunya Helen; Smarandache, Florentin (Communications in Mathematics and Applications, 2024)
We put forward the ideas of the neutrosophic implicative and \(n\)-fold implicative filters of BL-algebras. Additionally, we demonstrate that every implicative filter, including the \(n\)-fold implicative filter, is a neutrosophic filter. Moreover, we obtain an extension property for the neutrosophic implication. We then look at some comparable circumstances for neutrosophic implicative filters.